Channel Estimation in SC-FDMA using Flower PollinationAlgorithm (FPA) - Singh, Malook; Singh, Jaget; Singh, Sarvjit (International Journal of Computer Sciences and Engineering, 2025)
An important factor for any wireless communication system is estimation of its channel and channel parameters. In order to achieve good performance a communication receiver needs to know the impact of channel on received signal. This is called channel estimation. The motive of a channel estimation process is to minimize Mean Squared Error (MSE) between desired signal and received signal. Different channel estimation algorithm had been designed so as to achieve high performance. Using channel estimation algorithm impulse response of a channel and its behaviour can be approximated. By employing channel estimation techniques, coherent demodulation technique can be implemented at the receiver. In communication system for channel estimation a known signal sequence called pilot signals are inserted at specific location within the information signal. These symbol sequences allow receiver to extract channel attenuations and phase rotation estimates for each received symbol. By identifying channel parameters error in the received signal can be reduced. In this paper comparison of FPA optimization and without optimization with Rayleigh channel in 16, 32 and 64 bit modulation is performed.